Unique curriculum for gifted and talented persons: for what? (2014)
The National Planning Committee (1986) prepared a Blueprint on Education for the gifted and talented persons in Nigeria. In the Blueprint the Committee made a recommendation that the curricula for the gifted programme should be similar to the regular curriculum being provided in the 6-3-3-4 System of education. This paper tries to highlight how inadequate regular curriculum is to the gifted and talented persons and enumerates the reasons why it should be replaced with a unique curriculum.